2016
DOI: 10.1142/s0219477516500292
|View full text |Cite
|
Sign up to set email alerts
|

Taylor’s Law of Temporal Fluctuation Scaling in Stock Illiquidity

Abstract: Taylor's law of temporal fluctuation scaling, variance ∼ a(mean) b , is ubiquitous in natural and social sciences. We report for the first time convincing evidence of a solid temporal fluctuation scaling law in stock illiquidity by investigating the mean-variance relationship of the high-frequency illiquidity of almost all stocks traded on the Shanghai Stock Exchange (SHSE) and the Shenzhen Stock Exchange (SZSE) during the period from 1999 to 2011. Taylor's law holds for A-share markets (SZSE Main Board, SZSE … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Taylor's law can further be extended to higher orders using the k-th vs. the j-th cumulants [35], where the special case of k = 2 and j = 1 recovers the convention expression of Taylor's law. In addition, there is evidence showing that stock illiquidity, a nonadditive quantity, also complies with Taylor's law of temporal fluctuation scaling [36]. Here, we investigate the high-frequency illiquidity time series of Chinese stocks and confirm the presence of Taylor's Law of ensemble fluctuation scaling in stock illiquidity.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Taylor's law can further be extended to higher orders using the k-th vs. the j-th cumulants [35], where the special case of k = 2 and j = 1 recovers the convention expression of Taylor's law. In addition, there is evidence showing that stock illiquidity, a nonadditive quantity, also complies with Taylor's law of temporal fluctuation scaling [36]. Here, we investigate the high-frequency illiquidity time series of Chinese stocks and confirm the presence of Taylor's Law of ensemble fluctuation scaling in stock illiquidity.…”
supporting
confidence: 59%
“…We further observed that Taylor's scaling exponents of stock illiquidity are not related to the ensemble mean and ensemble variety of stock returns. Our analysis unveiled a new scaling law of financial illiquidity that complements Taylor's temporal fluctuation scaling law of illiquidity [36].…”
Section: Relationship To Ensemble Returns and Dispersionsmentioning
confidence: 57%
“…Most but not all empirical estimates of TL's slope fell between one and two (see Fig 2 in [25]). TL has also been verified for non-biological variables such as crime incidents [26], stock illiquidity [27], prime numbers [28], and tornado outbreaks [29]; in this last case, the slope exceeded four. Several models have been proposed to study the biological or statistical mechanisms of TL [3032].…”
Section: Introductionmentioning
confidence: 99%